The use of vacuum residue as a potential rejuvenator in reclaimed asphalt pavement: Physical, rheological, and mechanical traits analysis - Al-Saffar, Zaid Hazim; Eltwati, Ahmed; Essam Aziz, Ehab; Yaacob, Haryati; Abdulsattar Dawood, Halah; Putra Jaya, Ramadhansyah; S. Al Jawahery, Mohammed; Shaffie, Ekarizan (MDPI, 2023)
Asphalt recycling technology with a high content of reclaimed asphalt pavement (RAP) is becoming more important as the price of paving materials rises and sustainable development and environmental conservation rules become more rigorous. Nevertheless, road authorities in numerous countries still prohibit the utilisation of RAP in asphalt mixes due to the negative impacts of RAP on the performance of asphalt mixtures. Consequently, different rejuvenators have been introduced to reinstate the original attributes of aged asphalt to resolve this issue. This study incorporated vacuum residue (VR) into mixtures with 40% RAP. The physical, rheological, and mechanical traits of the resultant samples were assessed. The results show that the 7.5% VR rejuvenator minimised the RAP asphalt ageing impact. Furthermore, the rejuvenating agent demonstrated physical and rheological rehabilitative benefits for the aged asphalt. The mechanical attributes of the rejuvenated samples were also enhanced compared to the virgin asphalt (VA) specimens.